Design and strength reduction factors calibration of adhesive anchors embedded in thin concrete members. (June 2022) - Tarawneh, Ahmad N.; Saleh, Eman; Dwairi, Hazim M.; Majdalaweyh, Sereen A.
Abstract: This study presents and evaluates the safety level in the design procedure proposed for adhesive anchors in thin concrete members with full embedment depth under tensile and shear loads, to help in adopting the design models in building codes. In addition, the study provides calibration for the strength reduction factors. Based on the results of a comprehensive reliability analysis using the First-order reliability method (FORM) and a 3.5 selected reliability index threshold, strength reduction factors ( ϕ ) of 0.65, 0.60, and 0.55 are proposed for adhesive anchors under tensile loading for anchors class I, II, and III respectively. An Anchor class represents the anchor tensile capacity sensitivity for installation as per ACI 318-19. The study also proposes ϕ factor of 0.75 for adhesive anchors under shear load. The FORM results and the adequacy of the proposed strength reduction factors are verified using Monte Carlo-based reliability analysis. The results indicate that the current ACI 318-19 strength reduction factors can be safely used for the design of adhesive anchors in thin concrete members as they result in a slightly higher reliability index than the proposed ϕ factors in this study.